Processing of a multi-representational science passage by ESL learners - Nurjanah Mohd Jaafar; Siew, Ming Thang (Penerbit Universiti Kebangsaan Malaysia, 2020)
Verbal input is integral and is the core component in any language learning materials. As such, despite the incorporation of non-verbal input to facilitate language learning, language learners, more often than not, give attention more to the verbal components as opposed to the non-verbal ones. This paper reports on a study undertaken to examine 28 ESL undergraduates’ eye fixations when reading a science passage in English with an accompanying diagram. The data collection involves two stages. The first stage concerned the reading of the science passage and the second stage comprised short retrospective interviews conducted to explore the reasons behind the learners’ processing. Results of the eye tracking analysis indicate that similar to the processing of language learning materials, the ESL learners’ processing of the science passage was also mainly focused on the text (henceforth, “heavily text-based”). Findings from the retrospective interviews indicate that although a heavily text-based processing strategy was evident, most of the learners found the graphic input helpful. Analysis of the interviews also revealed that some learners were not aware of the strategies that they employed during the reading process. Although the eye tracking data imply that the ESL learners lacked the awareness and strategy to read and process multi-representational science texts in English effectively, the interviews suggest that they were aware of the potential and benefits of processing the accompanying diagram for overall comprehension. Effective design principles for multi-representational materials are suggested to promote more strategic processing among learners.